(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
Developmental dyslexia is a specific learning disorder that makes reading difficult and involves deficits in phonological processing, as well as difficulties and slow processing in other language skills (Wagner, R & Torgesen, J, 1987). A child with dyslexia has trouble reading, spelling and writing, it may also have difficulties with math and social skills, although it is important to note that dyslexia is not related to intelligence (ASHA). The contingency caused by the COVID-19 pandemic prompted the telemedicine and teleeducation processes to offer their services using ICT information and communication technologies, an alternative that we used to intervene in the case of an 8-year-old girl with developmental dyslexia, a disorder that has twice prevented him from advancing to the grade level. Synchronous and asynchronous encounters were held twice a week through the “meet” platform for three months, where a total of 22 sessions were held using a patient- and family-centered approach, with objectives directed at the girl and the child. parent training and support network. At the end of the intervention, there were significant advances in the acquisition process that allowed the girl to go from a clumsy reading of the alphabet to a reading of complex sentences.